Association of adherence to the Chinese version of the MIND diet with reduced cognitive decline in older Chinese individuals: Analysis of the Chinese Longitudinal Healthy Longevity Survey - Wenjian Lin; Xiaoyu Zhou; Xueyuan Liu (Elsevier, 2024)
Background: Current evidence suggests that the Mediterranean-Dietary Approaches to Stop Hypertension (DASH) diet intervention for Neurodegenerative Delay (MIND) is associated with a reduced risk of cognitive impairment among North American and Oceanian populations. However, there has been limited exploration of whether this association extends to the Asian population. This study aimed to assess the correlation between the Chinese version of the MIND (cMIND) diet and cognitive impairment in older Chinese individuals. Methods: We utilized data from the 2008 wave of the Chinese Longitudinal Healthy Longevity Survey. Participants aged ≥65 years with normal cognitive function at baseline were enrolled. The cMIND diet score (cMINDDS) was calculated by assessing dietary patterns based on survey responses. The Chinese version of the Mini-Mental State Examination (MMSE) was employed to diagnose cognitive impairment in participants. We stratified the analysis by cMINDDS and conducted additional sensitivity analyses. Results: The cohort consisted of 6411 participants. Over a 3-year follow-up, 1165 (18.6%) individuals who initially had normal cognitive function developed cognitive impairment. A linear association was observed between cMINDDS and cognitive impairment. The increased cMINDDS was associated with a reduced risk of cognitive impairment (quartile 1 vs. quartile 4: the adjusted odds ratio [OR] = 0.77, 95% confidence interval [CI]: [0.60, 0.97], p trend = 0.023). Regarding food composition, higher consumption of fresh fruits and nuts was associated with a decreased risk of cognitive impairment (OR = 0.77, 95% CI: [0.66, 0.89] and OR = 0.70, 95% CI [0.58, 0.86], respectively). Conclusions: Adherence to the cMIND diet was associated with lower risks of cognitive impairment in older Chinese individuals. The cMIND diet, based on the MIND dietary pattern, could serve as a preventive measure against cognitive impairment.